21ST CENTURY HISTORICAL LITERACY WITH A MODERN PERSPECTIVE: LITERASI SEJARAH ABAD 21 DENGAN PERSPEKTIF MODERN - Merina; Leo Agung (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The 21st-century historical literacy is a significant aspect in the contemporary historical study, where the narrative, production, and consumption of historical knowledge are influenced by technology and societal changes. This article intends to analyse historical literacy theory through the lenses of current scholars, highlighting how historical narratives today are constructed, debated, and applied in a global context. The research utilizes a library research methodology with a discourse analysis approach to current literature on historical literacy. It focuses on how the narratives of history are shaped by modern media and the critical role of digital technology in spreading historical knowledge. Historical literacy theory now demands active engagement with digital tools, critical thinking, and a reflective understanding of diverse historical contexts. This article also provides references from various international sources, focusing on research conducted between 2019 and 2025.